CFD numerical simulation of standalone sand screen erosion due to gas-sand flow - Alghurabi, A. (Elsevier B.V., 2021)
Solid particles entrained in produced gas cause erosive damage in production and transportation facilities, that may eventually impact any process safety. The main purpose of this research is to determine the point on the Standalone screen (SAS) surface, where erosion rate is critical and to evaluate the uncertainties in the calculations and predictions of sand screen erosion utilizing CFD numerical simulation. A k-epsilon model was implemented to solve gas flow behavior and Discrete Phase Model (DPM) was used to track solid particles. The results of DPM were then introduced to conduct erosion simulation on the SAS utilizing four erosion equations. A full presentation of particle velocity vectors, particle velocity streamlines, total pressure contours and wall shear stress contours on the screen surface are presented and discussed. Additionally, the particle traces and path-lines are also demonstrated based on particles residence time as part of the particlesâ trajectories. The erosion rates and erosion patterns from the four erosion equations, have shown similarities in their response to the change of sand characteristics. Considering the change in solid particles properties, a good agreement between CFD predictions and published data is achieved. This research can be used as a basis to offer safe operating guidelines for wells that are completed using standalone sand screens (SAS). Â© 2020 Elsevier B.V.